國中學生面對網路謠言之回應行為初探：以 Facebook 謠言訊息為例 Responses of Junior High School Students to Internet Rumors: A Case Study of Facebook Post - 黃慧宜 Hui-I Huang; 周倩 Chien Cho (National Taiwan Normal University, 2019)
本研究以國中學生為對象，探討學生面對疑似網路謠言訊息時的態度與行為，希望藉此瞭解學生對於網路謠言訊息之因應方式，以提供教育工作者或未來研究者參考。本研究以問卷調查法進行，蒐集臺灣北、中、南部地區共 578 名國中學生樣本所填寫之問卷，研究結果如下：一、學生認為在所有常用的網路服務或網路媒介中，幾乎都能察覺網路謠言的存在；二、學生普遍具備尋找線索進行資訊可信度判斷的能力，也能區分不同線索的重要性，但卻不一定能夠利用這些線索正確判斷網路訊息的真偽；三、學生對於網路謠言的有趣性感受與可信度判斷評價有關，且不會因謠言類型的不同而產生改變；四、學生最常使用的網路謠言處理方式為「看看就算了」，大部分傾向不處理，不會主動查證、澄清，但通常也不會傳播謠言。此外，學生的處理行為也會依網路謠言訊息的類型而不同，如學生較常查證或澄清的是「恐懼型謠言」，較常傳播的則是「新奇型謠言」；五、學生較常使用「與同學、朋友、家人討論」等方便快速的方式進行網路資訊驗證，較少選擇費時但更能確保結果正確無誤的資訊驗證方式。 This study aimed to explore and understand how junior high school students evaluate the credibility of online rumors, thereby helping educators and researchers to better understand their responses related to Internet rumors and their information evaluation behavior. The results were obtained from a survey of junior high school students in Taiwan (N = 578), which are as follows: (1) The students were aware of the Internet rumors appearing on the commonly used network services. (2) The students understood the process of evaluating the information obtained through online platforms; however, they lacked the ability of accurate and effective evaluation. (3) The personal interest of the students toward Internet rumors was related to the credibility evaluation process, and their evaluation remained unchanged when they encountered different types of rumors. (4) The students did not respond positively to Internet rumors or identify and clarify these rumors. They did not spread these rumors either. Students would use different approaches based on the type of rumors. For example, students were more likely to identify or clear bogie rumors and spread curiosity rumors. (5) The students eager to evaluate the credibility of online information would use faster and easier approaches, such as discussing the rumor with their classmates, friends, or family instead of using time-consuming but effective approaches.